Pengaruh Beban Kerja, Kompensasi, dan Lingkungan Kerja terhadap Stres Kerja Karyawan - Inayat Hanum Indriati; Anista Widhayanti (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of workload, compensation, and work environment on the work stress of employees. The research was conducted from February to August 2022. This research is a quantitative study with a total of 70 respondents and the sampling technique used is the saturated sampling technique. Data was collected by means of interviews and questionnaires. The analysis technique uses multiple linear regression analysis with the help of SPSS 22.0 for windows. The results of this study indicate that partially the workload has a positive and significant effect on work stress, compensation has a negative and significant effect on work stress, , the work environment has a negative and significant effect on work stress. Workload, compensation, work environment simultaneously have a significant effect on work stress. Workload, compensation, and work environment simultaneously affect work stress by 20.6%, while the remaining 79.4% is influenced by other variables.